Dampak Pembangunan Jalan Bypass Pada Peningkatan Kesejahteraan Masyarakat Tambunan Balige - Joel Fernandez Panjaitan; Agus Suriadi; Randa Putra Kasea Sinaga (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The construction of the Bypass Road is one of the factors in facilitating regional development, besides that it will also facilitate the flow of traffic which of course will have both positive and negative impacts related to the land around the road. Symptoms that occur indicate that with the construction of the Balige Bypass road is in addition to spurring the growth and development of the areas around the road but also spur speculators, migrants and investors to reside and invest to open businesses along the Bypass road, which in turn is expected to improve the welfare of the people around the Balige Bypass road. The purpose of this study was conducted to determine and analyze the impact of the construction of the Balige Bypass road on the welfare of the Tambunan Balige community. This research is expected to add knowledge in knowing the impact of the construction of the Balige Bypass road on improving the welfare of the Tambunan Balige community and can be one of the reference materials for the government and related parties for improvements in improving community welfare, as well as information and reference materials for parties in need. This type of research is descriptive qualitative research. Data collection is done through observation, interviews and documentation. The results of this study indicate that the construction of the Balige Bypass road has opened up employment opportunities.